1993
DOI: 10.1037/0022-3514.64.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Perceiver self-presentational goals as moderators of expectancy influences: Ingratiation and the disconfirmation of negative expectancies.

Abstract: Self-fulfilling prophecy processes enable people to confirm their negative expectancies for others. The perceiver goal of ingratiation was hypothesized to alter this behavioral dynamic and thus lead perceivers to disconfirm their negative expectancies. In an interview setting, we manipulated interviewer Ss' expectancies and interaction goals. As anticipated, "no goal" interviewers were relatively cold and challenging toward their negative-expectancy applicants; as a result, these applicants performed somewhat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…Instead, participants in these conditions received instructions intended to induce a particular processing goal. We used a procedure adapted from Neuberg, Judice, Virdin, and Carrillo (1993). Just before participants were asked to write down their questions, participants in the accuracy-goal condition were told that ''extensive research has shown that when generating questions, professional negotiators tend to work hard to develop an accurate impression of the opposing person.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, participants in these conditions received instructions intended to induce a particular processing goal. We used a procedure adapted from Neuberg, Judice, Virdin, and Carrillo (1993). Just before participants were asked to write down their questions, participants in the accuracy-goal condition were told that ''extensive research has shown that when generating questions, professional negotiators tend to work hard to develop an accurate impression of the opposing person.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, while not manipulating expectancies specifically, Le found that interactants led to believe their partners were nonstigmatized, gay, or a person with AIDS, all reciprocated the levels of nonverbal involvement they encountered, (Neuberg, Judice, Virdin, & Carrillo, 1993) and other research indicating a tendency for perceivers to compensate and reciprocate anticipated behaviors in different situations (Honeycutt, 1989;Ickes, Patterson, Rajecki, & Tanford, 1982), an important notion to remember is that the primary relevance for the current study lays in the demonstration of the effects of expectancies on communication.…”
Section: The Effects Of Actual Communication On Nonverbal Responsementioning
confidence: 85%
“…Moreover, unrepresentative expectations can create self-fulfilling prophecies (Merton, 1948), whereby people behaviorally confirmÐ usually unintentionally and without aw arenessÐ the expectations held by others (for reviews, see Brophy, 1983;Darley & Fazio, 1980 ;Miller & Turnbull, 1986 ;Neuberg, 1996 ;Snyder, 1992). Self-fulfilling prophecies have been demonstrated not only within laboratory-based interview settings (e.g., Neuberg, 1989;Neuberg, Judice, Virdin, & Carrillo, 1993 ) but within ª real-worldº interview settings as well (e.g., Macan & Dipboye, 1990). They represent a particularly problematic form of expectation bias because interviewers can gain, through the self-fulfilling prophecy process, an unrepresentative reality on which to shape biased evaluations.…”
mentioning
confidence: 97%
“…First, an interviewer' s expectations may influence his or her verbal and nonverbal expressive behaviors. The interviewer may express positive feelings toward applicants for whom he or she holds favorable expectations and leak negative feelings toward applicants for whom he or she holds unfavorable expectations (Harris & Rosenthal, 1985;Ickes, Patterson, Rajecki, & Tanford, 1982;Neuberg et al, 1993 ;Snyder, Tanke, & Berscheid, 1977;Word, Zanna, & Cooper, 1974). Because the norms of social discourse often lead us to reciprocate others' behaviors with similar behaviors of our own (e.g., Goffman, 1959), applicants who benefit from the interviewer' s favorable expectations are likely to perform more positively than their counterparts who confront the relatively cold expressions associated with unflattering expectations.…”
mentioning
confidence: 98%
See 1 more Smart Citation